An Evaluation of Anatomic Referencing for Femoral Component Sizing Using Computed Tomography-Based Computer Modeling - Campbell, Brett; Weinberg, Max; Bischoff, Jeffrey; Scuderi, Giles R. (The Journal of Knee Surgery, 2024)
One of the critical steps in total knee arthroplasty is femoral component positioning and sizing. Historically, there was wider variability between femoral component sizes, necessitating the concepts of anterior referencing (AR) and posterior referencing (PR). With the introduction of smaller increments between sizes, the concept of anatomic referencing has been introduced to replace AR and PR. The intent of this study was to validate the concept of anatomic referencing and show that with 2 mm increments in femoral sizes, the femoral component can be placed flush to the anterior cortex while maintaining posterior condylar offset (PCO). Digital surface models were created using 515 femurs from an established computed tomography database. Virtual bone resections, component sizing and placement were performed assuming neutral mechanical axis and a cartilage thickness of 2 mm. The appropriately sized femoral component, which had 2 mm incremental sizes, was placed flush with the anterior cortex with restoration of the PCO. The anterior–posterior distance from the posterior surface of the component to the medial and lateral surfaces of the posterior condylar cartilage were measured. The medial condyle was the limiting condyle in the majority of cases (73%). The average medial gap after appropriate femoral component matching was 0.6 mm (0.39–1.41 mm) across all sizes. The overall average condylar gap was 1.02 mm. The most common femoral component was a size 7 (57.2 mm) and the average femoral AP width was 55.9 mm. Anatomic referencing with an implant system that has 2-mm increments in femoral component sizing provides an alternative to AR and PR without compromise. Anatomic referencing allows for perfect alignment of the anterior flange of the femoral component to the anterior cortex of the femur while restoring the native PCO to within 1 mm. This avoids having to choose between AR or PR when in between femoral sizes.
Keywords: implant; anatomic referencing; total knee arthroplasty